Financing Decision Significance, Capital Structure and Initial Yield Behaviour: Evidence from Finnish Commercial Property Markets - Salminen, Jaakko (My University, 2008)
Commercial property business has been blooming in Finland since the first major transaction was made abroad in 2002. In the mean time the capital structure of investments has developed to be always more debt-based and thus positive financial leverage is achieved. Historically seen, low interest rate level and increased liquidity have assisted such development. The past in the Finnish markets have led to a situation where financing plays a major role. In the other regional markets it has been already researched that by effective and suitable financing properties as an investment objective, can be made to be more attractive. For this purpose this study investigates the financing decision making process as a part of investment decision in the Finnish markets. Also the factors that affect the level of significance are researched. This study is done by exploiting the information collected by interviews and other gathered data of KTI. Despite of the small number of interviews the sample covers well the Finnish markets by interviewing almost one third of the active participants in the markets. Besides the qualitative part, this paper produces statistical results to prove the main finding of this paper. Risk level used to test hypotheses is to be 5 % (p≤0,05). Results of this study showed that despite of traditional theory of finance, commercial property investors integrate the financing decision into overall investment decision. The only factor that was close to risk level limitation was capital structure when investigating significant factors for financing significance were researched. In addition volatility behaviour compared with initial yield requirement gave statistically significant results with good explanatory level being around 20 %.
Keywords: Commercial Property; Financing Decision; Capital Structure; Initial Yield; Volatility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|